Strategic management accounting tools as a ‘package’: a case study / Hiruni Rathwatta and Tharusha Gooneratne - Rathwatta, Hiruni; Gooneratne, Tharusha (Universiti Teknologi MARA, 2021)
Drawing empirical evidence from a telecommunications firm in Sri Lanka this paper reports on a case study of how strategic management accounting (SMA) tools form a package. We deployed the qualitative method and case study approach, and in-depth face-to-face interviews with key personnel engaged in the practice of SMA in the firm and reviewed documents to collect data. Our findings indicated that the firm used a bundle of SMA tools relating to competitors, customers, cost, and performance, essentially as a package. Findings further suggested that the use of SMA tools as a package gives rise to crucial implications in the form of interactions and contradictions, which were managed through reconciliation statements, analysis of variances, discussions, meetings, and informal communications. This research contributes to the management accounting literature by developing novel insights on the notion of ‘SMA tools as a package’. From a theoretical stance, it offers a framework to explore SMA tools as a package, capitalizing on prior literature and field data from the case study firm. It also provides learning points to practitioners regarding the simultaneous use of a collection of SMA tools as a ‘package’ to support organizational decision making.